Analisis Faktor Abiotik Sumber Air Sumur di Lingkungan Kawasan Pesisir Pantai : Studi Kasus Kawasan Kampus Universitas Bengkulu - Samsul Bahri; Budi Harlianto; Helfi Eka Saputra; Apriza Hongko Putra; Mardhatillah Sariyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
University of Bengkulu is a communal area located on the west coast of Sumatra. The main water sources to support activities at UNIB come from shallow wells (dug) and deep wells (drilled). This study aims to analyze the physical and chemical parameters of dug and bore water wells in the environment of UNIB’s campus. Water quality testing for dug and bore wells includes several treatments. Water quality analysis using the Indonesian National Standard method. The results of water quality testing for dug and bore wells founded several physical and chemical parameters exceeding Class II water quality standards. The results of the testing of the quality of water in the TSS 1 dug well had exceeded the quality standard. The results of testing the quality of dug wells 1, 2, 3 and 4 pH and phosphate parameters had exceeded the quality standard. The results of testing the quality of dug 2 meter wells dug DHL had exceeded the quality standard. The results of the testing of the quality of water in a borehole 1 phosphate parameter had exceeded the quality standard. The results of water quality testing for boreholes 2 and 3 Fe parameters had exceeded the quality standard. Dug and bore well water sources in the UNIB environment can be used for drinking water, drinking freshwater fish, livestock, irrigating crops, and / or other purposes that require the same water quality as these uses. Keywords: Physical and Chemical Parameters, Deep Water, Shallow Water, Quality Standard